Teachers, School Boards, and the Power of Money: How the Right Wins at the Local Level. Issue 2 (2nd April 2016) - Schirmer, Eleni B.; Apple, Michael W.
Abstract: This article examines national conservative political advocacy groups' growing interest in local politics, and analyzes how they form alliances and gain political power. Following efforts to restrict collective bargaining for Wisconsin public employees, Kenosha school board members' attempts to legally protect teachers' rights provoked concern from nationally financed conservative groups. This article discusses why a small-town school board election attracted such attention, and the significance of increased attention to the local by these national groups.